Influence of Geometric Parameters of Tiny Blades on the Shroud of a Centrifugal Pump on the Cavitation Suppression Effect - Zhao, Weiguo; Zhou, Zhongliang (Frontiers in Energy Research, 2022)
In this paper, the effect of adding non-connected forms of tiny blades with different parameters of radial position, width and length to the shroud of the impeller on the cavitation performance of a centrifugal pump is researched. A modified SST k-ω turbulence model combined with the Zwart-Gerber-Belamri cavitation model is used for numerical simulation of the model pump. The results show that the numerical prediction of the original pump agrees well with the experimental results. Adding tiny blades with different radial positions, widths and lengths has a little effect on the pump head and efficiency at each working condition. Adding tiny blades near the impeller inlet has better suppression of cavitation in the initial stage, and adding tiny blades in the middle and backward position has better suppression effect on all stages of cavitation. There is an optimal tiny blade width to make the cavitation suppression effect optimal, and the optimal width of the model in this study is 3/4 of that of the main blade. The effect of tiny blade length on cavitation performance is little. The existence of tiny blades slightly increases the turbulent kinetic energy in the low turbulent kinetic energy region near the impeller inlet, significantly reduces the turbulent kinetic energy in the high turbulent kinetic energy region near the outlet, and reduces the overall pressure pulsation main frequency amplitude during pump operation, making its operation more stable.